Réponses

Meilleure réponse !
2014-09-21T14:50:20+02:00
B = 5 x (12 - 2 x 4 ) + 6 - 4 : ( 5 - 1 )
B = 5 x (12 - 8) + 6 - 4 : (4)
B = 5 x (4) + 6 - 1
B = 20 + 5
B = 25

C = 18 - 6 : ( 2 + 1 ) - 7 x 2 : 4
C = 18 - 6 : (3) - 14 : 4
C = 18 - 2 - 3,5
C = 18 - 5,5
C = 12,5
2014-09-21T15:02:07+02:00
B)=5(12-8)+6-2/4=5(4)+(24-2)4=20-22/4=(80-22)/4=58/4=29/2            C)=18-6/3-14/4=(216-24-42)/4=150/4=75/2  la formule est simple il faut donner la priorité aux ensuite aux multiplication et enfin aux divisions